Business Ethics and Accounting Information. An Analysis of the Spanish Code of Best Practice - Espinosa-Pike, Marcela (Journal of business ethics, 1999)
The main purpose of this article is to analyse one aspect of Spanish business ethics: the role of the transparency and quality of the economic and financial information given to meet the demands and requirements of shareholders. To that end we concentrate firstly on analysing the Spanish capital market and the situation of shareholders prior to the publication in February 1988 of the Code of Best Practice for Spanish Companies, drawn up by a Special Committee created at the request of the Ministry of Economy and Finance. We analyse the importance of the behaviour and actions of three groups which are fundamental to assuring quality and transparency of information: those who prepare financial statements, the Board of Directors (particularly the Audit Committee) and the external auditors. Finally, we look at the possible consequences of the Code of Best Practice on Spanish business ethics.